Analysis of Judges’ Considerations in Deciding Judicial Divorce at the Palu Religious Court - Alhamid Baharuddin; M. Taufan B.; Syahabuddin Syahabuddin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2020)
The aim of this paper is to discuss Judges’ consideration in making decision in the case of judicial divorce. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using grounded theory approach. The results showed that there were two basic considerations for judges in deciding a lawsuit for divorce at the Palu Religious Court Class 1A, namely written law and unwritten law. Written laws include Al-Qur'an, Hadith, Laws, and Compilation of Islamic Laws, while the unwritten law is the customs and values ​​that live in society. Based on the decision Number 452/Pdt.G/2019/PA.Pal, these laws were used as the basis for the judge's consideration in deciding this case, because continual disputes and quarrels occurred between husband and wife, that resulted to the separation of residence which has lasted for about 11 months, and it is no longer possible to live in harmony in the household.